2006
DOI: 10.1162/jiec.2006.10.3.57
|View full text |Cite
|
Sign up to set email alerts
|

Swedish Experience Using Environmental Accounts Data for Integrated Product Policy Issues

Abstract: Summary This article quantifies and ranks the environmental pressure caused by different product groups consumed in Sweden. This is done using information from economic and environmental statistics. An analysis for the year 1998 is performed for approximately 50 product groups using input‐output analysis. This type of analysis has some major advantages for integrated product policy (IPP) purposes: the underlying data are regularly updated, the data systems are being harmonized by international standards, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…According to the results, the building and real estate management sector is responsible for a significant part of the environmental impacts in Sweden. This finding is also confirmed by previous work (Ecocycle Council 2001; Palm et al 2006; Carlsson and Lilliehorn 2008), and similar results have been reported internationally (Huppes et al 2006; Tukker and Jansen 2006). Energy use, use of hazardous chemical products, generation of solid waste, emissions of gases contributing to climate change, and human toxicological impacts (e.g., NOx and particulates) are especially relevant for the sector.…”
Section: Conclusion and Reflectionssupporting
confidence: 91%
“…According to the results, the building and real estate management sector is responsible for a significant part of the environmental impacts in Sweden. This finding is also confirmed by previous work (Ecocycle Council 2001; Palm et al 2006; Carlsson and Lilliehorn 2008), and similar results have been reported internationally (Huppes et al 2006; Tukker and Jansen 2006). Energy use, use of hazardous chemical products, generation of solid waste, emissions of gases contributing to climate change, and human toxicological impacts (e.g., NOx and particulates) are especially relevant for the sector.…”
Section: Conclusion and Reflectionssupporting
confidence: 91%
“…As a part of the activities of the European Commission's Integrated Product Policy (IPP) Communication, for example, there was a need to identify key products and services produced and consumed within the European Union countries that impose significant environmental loads. The IO-LCA was recognized as an appropriate tool for identifying such hotspots at the EU and national-scales in these IPP projects (Huppes et al, 2006;Palm et al, 2006;Tukker and Jansen, 2006;Weidema et al, 2006). Indicators for IPP have also been suggested based on IO-LCA (Palm et al, 2006;Bjö rklund et al, 2007).…”
Section: Input-output and Hybrid Lcamentioning
confidence: 99%
“…Analysts, including ourselves when performing the Environmental Impacts of Products study, then often apply a shortcut and assume that imported goods and services are made with the same technology as those produced domestically (Hendrickson et al, 2006;Huppes et al, 2006;Palm et al, 2006). This can lead to serious errors (Peters and Hertwich, 2006a;2006b;Ghertner and Fripp, 2007;Weber and Matthews, 2007; compare also Ahmad, 2003;Ahmad and Wyckoff, 2004).…”
Section: Implications Of Existing Data Limitationsmentioning
confidence: 99%